A responsabilidade da pessoa jurídica por atos de improbidade administrativa e por atos lesivos à Administração Pública - Cardoso, Raphael de Matos (2018)
The determination of morality (which has as antitheses the impropriety and the corruption), especially since the promulgation of Law 12.846/2013, received new focus and was even transported to the objective field, which motivated this study, whose objects of investigation are: the difference between civil responsability and administrative responsability, and the determination of the legal nature of the sanctions applied under the latter, as well as its place in administrative sanction law, where the administrative wrongdoing is also situated, presupposes the subjective element. Having analyzed these matters, we place the legal person in its proper place regarding infractions and administrative sanctions under the Law 8.429/92 and the Law 12.846/2013